ANALISIS BIAYA SIKLUS HIDUP GEDUNG KOMITE OLAHRAGA NASIONAL INDONESIA (KONI) KABUPATEN TAPIN - Hendra Cahyadi; Abdurrahman; Sapto Priyo Atmojo (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The Indonesian National Sports Committee Building or the abbreviation KONI Tapin Regency has been established since 2012 and has been operating for almost 10 years. So that the function of the building does not decrease during the design life, routine maintenance is needed. However, the maintenance carried out on the building so far has only been carried out if there is damage or as needed. Therefore, it is necessary to study life cycle costs at KONI Tapin Regency to analyze operating costs throughout the life of the plan. The purpose of this study was to determine the life cycle costs of the Tapin Regency Indonesian National Sports Committee (KONI) Building for 2021-2035 and to determine the largest maintenance costs during the life cycle of the Tapin Regency Indonesian National Sports Committee (KONI) Building for 2021-2035. The research method used is the life cycle cost analysis method which is equipped with interviews with building managers and field identification. The research results obtained are, the total maintenance costs for the years 2021 to 2035 with an inflation rate of 4.50% is IDR. 1,939,225,599. For maintenance costs per year of IDR. 129,281,707 for 15 years. The biggest maintenance cost during the life cycle of the Tapin Regency Indonesian National Sports Committee (KONI) Building for 2021-2035 is the electrical component of IDR. 51,329,237 per year or 39.703%. While the smallest maintenance costs are mechanical components of IDR. 3,257,850 per year or 2.520% of the total maintenance cost.